Trajetórias de vida de pessoas com deficiência e educação física escolar - Camargo, Laureen Lopes (2018)
The discussion scenario for Special Education (SE) and Inclusive Education (IE) is a reality today and means that it does not occur only in the theoretical field. The difficulties and challenges are related to different aspects shown by many studies that verify that, unfortunately, exclusionary situations in school everyday. The same scenario is noted when we focus in school physical education (SPE). Therefore, the topic of this research is related to SPE and SE. The general objective is: to analyze the exclusion factors of people with disabilities (PWD) in SPE. The specific objectives are: 1) to describe and study the life trajectory of PWD focusing on lived experiences during physical education (PE) classes at school; 2) to study the relation between SPE of PWD and their involvement with sports; and 3) to analyze the PWD conception of PE. The theoretical framework is based on Dermeval Saviani's Historical-Critical Pedagogy (HCP), as well as EE studies such as Jannuzzi (2004a, 2004b) and PE studies such as Chicon (2015), Darido (2003) and Castellani Filho (2003), which will help to discuss its contextualization, conceptions, purposes and contents. The chosen referential is the thematic oral history, focusing on five axes to conduct the interviews. The selected collaborators are four adult educated athletes, with ages varying from 17 to 63 years, who play in adapted teams in the city of Sorocaba and are already attending school as a disability person. The analysis of the interviews identified and classified the contents that most appeared at the narratives. After that, constructed data was interpreted according to the theoretical framework of the research, pursuing to answer the proposed questions. Finally, it was possible to realize a concrete analysis of the real-life movement of the PWD, considering their past in the SPE, identifying as exclusion factors: 1) the teachers' approach; 2) the dissemination of content without a dialectical interface with the social function of SPE; 3) the fragility in legitimation of SPE’s purposes; 4) the discrimination and society’s difficulty in understanding people instead of judging someone by their disabilities; 5) the unpreparedness in some professionals training. It should be emphasized that it was not intended to assign value judgments to historical moments of the SPE, but to perform a critical analysis to understand such factors, assuming a political position of discussing the reality of PWD in these classes through their own trajectories: “Nothing about us, without us!”. It is expected to contribute with a quality education and encourage further studies focused on educational practices, which prepare individuals to intervene and overcome barriers that are put by society and thus ensure everyone’s right to acquire knowledge and contents about body culture, aiming a truly inclusive SPE.